1997
DOI: 10.1046/j.1365-2141.1997.d01-2103.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometry of leucocyte alkaline phosphatase in normal and pathologic leucocytes

Abstract: Summary. Leucocyte alkaline phosphatase (LAP) is an enzyme expressed on the external aspect of the neutrophilic granulocyte plasma membrane, and represents a specific marker for the fully differentiated granulocyte. In this report we characterize 1B12.1, a monoclonal antibody raised against human bone alkaline phosphatase, by its ability to recognize the LAP protein. As assessed by Western blot analysis, following electrophoresis under non-reducing conditions, the antibody specifically reacts with LAP upon for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…AP is broadly expressed in many pre-and postnatal tissues, and in different cell types such as osteoblasts 37 , embryonic stem cells 38 , bone marrow stroma cells 39 , liver and kidney cells 40 , granulocytes 41 and B cells 42 ; however, in postnatal mouse striated muscles, AP is expressed only by vessel-associated cells, in both endothelial cells and pericytes, as previously reported 9,[14][15][16] , and exhaustively confirmed in this work through a variety of histochemical and immunochemical methods. Most importantly, by using virtually all possible experimental approaches, we demonstrated that both AP and Cre expression are invariably absent in quiescent satellite cells, as well as in proliferating and differentiating myogenic cells in vitro or in vivo, even after cardiotoxin-induced damage.…”
Section: Discussionmentioning
confidence: 99%
“…AP is broadly expressed in many pre-and postnatal tissues, and in different cell types such as osteoblasts 37 , embryonic stem cells 38 , bone marrow stroma cells 39 , liver and kidney cells 40 , granulocytes 41 and B cells 42 ; however, in postnatal mouse striated muscles, AP is expressed only by vessel-associated cells, in both endothelial cells and pericytes, as previously reported 9,[14][15][16] , and exhaustively confirmed in this work through a variety of histochemical and immunochemical methods. Most importantly, by using virtually all possible experimental approaches, we demonstrated that both AP and Cre expression are invariably absent in quiescent satellite cells, as well as in proliferating and differentiating myogenic cells in vitro or in vivo, even after cardiotoxin-induced damage.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate granulocyte activation in myeloproliferative disorders, we measured LAP, 24,25 CD16, 25 and CD157 26 expression levels on circulating granulocytes.…”
Section: Flow Cytometry Analysis Of Circulating Granulocytesmentioning
confidence: 99%
“…27 CD11b, CD38, CD14, ICAM-1, and integrin ␣-5 were measured by flow cytometry using specific monoclonal antibodies (Becton Dickinson, Franklin Lakes, NJ). 28 The nitrobluetetrazolium (NBT) reduction assay was performed on extracts of phorbol myristate acetate-stimulated cells, 20 and the percentage of NBT ϩ cells was determined as described. 20 Western blot analysis, JNK kinase activity, and determination of cytokine secretion and gel retardation assays Extracts of NB4 cells (from 3 ϫ 10 6 cells) were subjected to Western blot analysis as reported.…”
Section: Chemicalsmentioning
confidence: 99%